The Effect of Knowledge Sharing and Supply Chain Management on Opportunity Recognition through Management Skill in the Food Industry of SMEs - Ratih Indriyani; Anis Eliyana; Achmad Sobirin; Steven Nathanael (International Journal of Supply Chain Management, 2020)
The ability to manage and understand opportunities for business development is necessarily important for the operators of the food industry, supported by knowledge sharing activities between the managers and employees and supply chain management. This study aimed to determine the effect of knowledge sharing and supply chain management on opportunity recognition skill through management skill in the food industry in Surabaya. This study involved 100 food business owners and managers in Surabaya as the research samples. This study was conducted by examining the knowledge sharing, opportunity recognition skill, and management skill, and the data obtained were analyzed using PLS. As a result, knowledge sharing was found to have a significant effect on opportunity recognition skill through management skill.